Effects of sleep restriction on metabolism-related parameters in healthy adults: A comprehensive review and meta-analysis of randomized controlled trials. (June 2019) - Zhu, Bingqian; Shi, Changgui; Park, Chang G.; Zhao, Xiangxiang; Reutrakul, Sirimon
Summary: This review aimed to provide a comprehensive examination of the effect of sleep restriction on metabolism-related parameters by synthesizing the emerging, best evidence. A systematic search was conducted in six electronic databases from inception to January 2018. We identified 41 randomized controlled trials using sleep restriction intervention. The outcomes included: subjective hunger, appetite-regulating hormones, changes in brain activity, energy intake and expenditure, weight change, insulin sensitivity or resistance. Sleep restriction resulted in a significant increase in subjective hunger on a 100 mm scale (mean difference = 13.4, p  < 0.001). Participants consumed 252.8 more kcal/d ( p  = 0.011) under sleep restriction than under normal sleep. Partial sleep restriction resulted in a 0.34 kg weight gain ( p  = 0.003). Sleep restriction also decreased insulin sensitivity (standardized mean difference = −0.70, p  < 0.01). Significant changes in brain activity in response to food stimuli were observed under sleep restriction, particularly regions related to cognitive control and reward. Overall, we did not find strong evidence supporting the significant impact of sleep restriction on mean leptin or ghrelin levels or energy expenditure. Findings from this review enhanced our knowledge about the detrimental effects of sleep restriction on metabolism and provided novel directions in preventing metabolic diseases including obesity and diabetes.